Case Report: Persistent Primitive Hypoglossal Artery Accompanied by a Basilar Bifurcation Aneurysm Treated by Y-Stent-Assisted Coil Embolization - Zhang, Longhui; Chen, Xiheng; Jia, Luqiong; Dong, Linggen; Wang, Jiejun; Liu, Peng; Lv, Ming (Frontiers in Neurology, 2021)
Carotid–vertebrobasilar anastomoses, known as presegmental arteries in the embryonic period, supply blood from the internal carotid artery (ICA) to the primitive vertebrobasilar system. Persistent primitive hypoglossal artery (PPHA) is the second most common primitive communication between the ICA and the basilar artery (BA). The incidence of this persistent carotid–vertebrobasilar anastomosis is 0.027%–0.26%. Due to an anomalous structure of the vessel wall, posterior circulation blood supply from the ICA, and exposure to unusual hemodynamic stress, PPHA patients often have intracranial anomalies, such as aneurysms. PPHA disrupts hemodynamic stability between the carotid and vertebrobasilar system. Although the incidence of PPHA accompanying intracranial aneurysms is approximately 26%, there are few reports of basilar bifurcation aneurysm. To better characterize PPHA, we created a schematic to summarize this type of carotid–vertebrobasilar anastomosis . We report a patient with an unruptured wide-neck basilar bifurcation aneurysm accompanied by right PPHA. Although vertebral arteries were present, both were hypoplastic. We advanced a microcatheter via the PPHA, with the help of Y-stent-assisted coiling and successfully treated this aneurysm. Follow-up 6 months after the endovascular treatment using brain digital subtraction angiography (DSA) showed no recanalization of the aneurysm. To our knowledge, the use of Y-stent-assisted coiling to treat PPHA accompanied by basilar bifurcation aneurysm has not been reported previously. Here, we describe the details of the patient’s clinical course with a brief review of the relevant literature.